Maximum Ride: The angel experiment - JAMES PATTERSON; JAMES PATTERSON (New york little brown and company, 2005)
follows fourteen-year-old Max and her "flock"$1 (Bfive other genetically engineered human-avian hybrids$1 (Bwho have escaped a sinister lab called "the School". When Erasers (wolf-human hybrids) kidnap the youngest member, Angel, the flock embarks on a dangerous mission to save her, ultimately taking them from the mountains to New York City. s
Keywords: The flock lives on the run after escaping a horrific scientific laboratory known as "The School".; family, loyalty, and love are the most important things in life, overcoming any hardship or danger